Copolymers of 2,5-furandione : synthesis, characterization and properties in composite dynamic membrane applications - Dowler, Norman Arthur (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1986.